ENROLLMENT READINESS AMONG THE PARENTS OF MADRASAH GOING CHILDREN WITH E-LEARNING FACILITIES IN MAIZBHANDAR AHMADIYYA EMDADIA MADRASAH, CHATTOGRAM, BANGLADESH (American International Journal of Education and Linguistics Research, 2021)
During the Covid-19 pandemic, madrasahs of rural areas in Bangladesh are unable to conduct regular curricular activities in person. Despite government encouragement very few institutions have introduced online classes; madrasahs of rural areas have faced challenges to introduce online classes due to the lack of technological facilities and their uses. However, if the parents are not ready to accept ICT to use in educational purpose, they will not be interested in enrolling their children in those Madrasahs which have encouraged online education. This study aims to measure the factors behind the enrollment readiness among the parents of madrasah going children to Maizbhandar Ahmadiyya Emdadia Madrasah in Chattogram district of Bangladesh. In line with the quantitative approach, researchers developed an close-ended questionnaire based on four variables of the Technology Acceptance Model (TAM), namely, Perceived Usefulness (PU), Perceived Ease-of-Use (PEOU), Intention to Use (IU) and Usage Behavior (UV). Therefore, the findings of this research will show how enrollment in rural areas can be increased to facilitate ICT-enriched classrooms. In addition, the findings will lead the researchers and policy makers to investigate the technological acceptance of the teachers and students of rural madrasahs for the advancement of the madrasah education system.